Influencing factors of corticomuscular coherence in stroke patients - Gao, Zhixian; Lv, Shiyang; Ran, Xiangying; Wang, Yuxi; Xia, Mengsheng; Wang, Junming; Qiu, Mengyue; Wei, Yinping; Shao, Zhenpeng; Zhao, Zongya; Zhang, Yehong; Zhou, Xuezhi; et al. (Frontiers in Human Neuroscience, 2024)
Stroke, also known as cerebrovascular accident, is an acute cerebrovascular disease with a high incidence, disability rate, and mortality. It can disrupt the interaction between the cerebral cortex and external muscles. Corticomuscular coherence (CMC) is a common and useful method for studying how the cerebral cortex controls muscle activity. CMC can expose functional connections between the cortex and muscle, reflecting the information flow in the motor system. Afferent feedback related to CMC can reveal these functional connections. This paper aims to investigate the factors influencing CMC in stroke patients and provide a comprehensive summary and analysis of the current research in this area. This paper begins by discussing the impact of stroke and the significance of CMC in stroke patients. It then proceeds to elaborate on the mechanism of CMC and its defining formula. Next, the impacts of various factors on CMC in stroke patients were discussed individually. Lastly, this paper addresses current challenges and future prospects for CMC.